PREPARING STUDENTS TO MEET THE DEMAND FOR 21 CENTURY SKILLS: OPPORTUNITIES, CHALLENGES, EXPECTATIONS - Самойленко, Н. (Proceedings of Kyiv Aviation Institute. Series: Pedagogy. Psychology, 2018)
The article introduces the study of English as a lingua franca (ELF). The author outlines why ELF is an important area of research. The different ways of understanding how English is used and taught in universities today in Master’s degrees academic writing learning process are described. The role of students’ digital skills and new trends of online education implementation in the foreign language teaching process in a higher educational institution are highlighted. The problem of professional online tutor preparation was determined. The opportunities for implementation of online education for improvement of higher pedagogical education in the foreign language teaching process are revealed. Professional online tutor training curriculum was specified. The opportunities for virtual education and communication are described. Necessity to generalize today’s students’ skills for providing education online course is considered. Technology influence on language learning process, new ways of teaching and learning: the students’ interacting in groups or working on a monologue or story; involving students to record podcasts, audio files, developing students’ written skills in blogs and wikis are investigated. On-line professional training courses on leading on-line platforms as an up-today trend in education are pointed out. The examples of on-line courses for students and teachers on leading on-line platform «Future Learn» for 2017-2018 yy. are presented. The digital tools, which we can used learners for presenting their digital identity to the world by using digital badges, digital CVs to show off what the students can do are summarized.